1985
DOI: 10.1037/0736-9735.2.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Orality and depression: An empirical study.

Abstract: Despite much theoretical speculation and some indirect evidence, no study has empirically assessed the relationship of orality to depression. In the present investigation, two separate samples of male college students (M = 276; N 2 = 141) completed both the Rorschach test and the Depression Experiences Questionnaire (DEQ). More DEQ items correlated significantly with a Rorschach orality measure than would be expected by chance, but the magnitude of these correlations was small. Item analysis suggests that depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Along with a general measure of depression, the DEQ provides separate scores for three factors; Dependency (anaclitic depression), Self-Criticism (introjective depression), and Efficacy. Bornstein et al (1985) reported significant correlations between dependency and orality in Sample 2 ( r = .17, p < .05), selfcriticism and orality in both samples (Sample 1, r = .16, p < .005; Sample 2, r = .14, p < .05) and the total DEQ score and orality in both samples (Sample 1, r = .17, p < .005; Sample 2, r = . 25, p < .001).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Along with a general measure of depression, the DEQ provides separate scores for three factors; Dependency (anaclitic depression), Self-Criticism (introjective depression), and Efficacy. Bornstein et al (1985) reported significant correlations between dependency and orality in Sample 2 ( r = .17, p < .05), selfcriticism and orality in both samples (Sample 1, r = .16, p < .005; Sample 2, r = .14, p < .05) and the total DEQ score and orality in both samples (Sample 1, r = .17, p < .005; Sample 2, r = . 25, p < .001).…”
mentioning
confidence: 85%
“…(p. 216) Despite the acceptance of this conjecture within psychoanalytic theory, the relation of orality to depression has been the subject of little empirical investigation. Bornstein, Poynton, and Masling (1985) attempted to link the concepts of orality and depression; they administered the group Rorschach test and the Depressive Experiences Questionnaire (DEQ; Blatt, D' Afflitti, & Quinlan, 1976;1979) to two samples of male college students (n = 276, n = 141). The Rorschach had previously provided a reliable measure of orality through content analysis, with responses that allowed either oral percepts or dependent percepts to be scored (Masling, Rabie, & Blondheim, 1967).…”
mentioning
confidence: 99%
“…From the initial sample of 101 students, 16 were excluded because they failed to give at least 20 responses to the Rorschach (see Bornstein et al, 1985) and four because of invalid DEQ or CES-D protocols. Of the remaining 81 (final sample at T1), 67 agreed to participate at T2, 12 failed to give a correct identification to allow a matching to T1 protocol, and three were eliminated due to invalid DEQ or CES-D protocols, resulting in a final sample, at T2, of 52 participants.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…A recent study by Bornstein et al (1985) further supports the linkage of oral dependency and depression. In two samples of normal (i.e., not clini cally depressed) male college students, a significant, positive relationship was found between scores on a Rorschach measure of oral dependency and depression (DEQ) scores.…”
Section: Dependency and Depressionmentioning
confidence: 74%
“…Among the more promising of these is Blatt's (1974) discussion of levels of object representations in the depressive syndromes. This model has been reviewed by Bornstein, Poynton, and Masling (1985). Blatt (1974) distinguished subtypes of depression based on the individ ual's level of object representations and degree of self-other differentiation.…”
Section: Dependency and Depressionmentioning
confidence: 99%